2012
DOI: 10.1111/j.1440-1681.2012.05668.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of adenosine on myocardial perfusion in patients treated with primary percutaneous coronary intervention for acute myocardial infarction

Abstract: The present study investigated the effects of intravenous adenosine on myocardial perfusion and segmental contractile function when used as an adjunct of primary percutaneous coronary intervention (PCI) in patients with acute ST segment elevation myocardial infarction (STEMI). Patients were randomly assigned to receive intravenous adenosine (n = 35) or saline (n = 34) within 12 h of STEMI. Myocardial contrast echocardiography (MCE) and velocity vector imaging (VVI) were performed 7 days after primary PCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…In a clinical trial, a high dose of intracoronary adenosine given during percutaneous coronary intervention (PCI) did not reduce infarct size [638]. However, a later study provided evidence for contrasting beneficial effects of adenosine under similar conditions [639]. Intracoronary administration of adenosine, but not of nitroprusside, resulted in a significant improvement following acute MI [640].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…In a clinical trial, a high dose of intracoronary adenosine given during percutaneous coronary intervention (PCI) did not reduce infarct size [638]. However, a later study provided evidence for contrasting beneficial effects of adenosine under similar conditions [639]. Intracoronary administration of adenosine, but not of nitroprusside, resulted in a significant improvement following acute MI [640].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…In this study we found that the elevated cardiac microvascular flow in anaemic fetuses was achieved by faster average microvascular blood flux rate, but that MBV fraction at rest was not altered by chronic fetal anaemia. This finding is unexpected as MBV typically increases when growth or remodelling increases coronary flow in adults (Di Bello et al 2003;Indermuhle et al 2006;Ikonomidis et al 2010;Santos et al 2010;Wang et al 2012). Fetal capillary widening in concert with decreased haematocrit can explain the increased coronary microvascular flow observed by MCE.…”
Section: Discussionmentioning
confidence: 95%
“…Also, Sakuma et al [31] in a group of patients with first anterior myocardial infarction, after intravenous administration of a high dose of adenosine (150 ug/kg/min started 5 min before the beginning of the primary PCI and continued for up to 1 h) observed enhanced ST segment resolution 90 min after recanalization, reduced no-reflow ratio, preserved left ventricular systolic function and prevented left ventricular remodeling at 6 months after primary PCI. Wang et al [32], after intravenous adenosine infusion (50 μg/kg/min for 3 h) in patients with acute ST segment elevation noted improved myocardial perfusion, segmental wall motion and global contractile function.…”
Section: Discussionmentioning
confidence: 99%